Metal lithium composite electrolyte negative electrode, preparation method and application

By covering fluorine -containing acid -containing acid on the electrolyte of oxide and combining lithium melting lithium to form a high -interface energy and high -conductivity interface, solve the problem of the interface resistance and instability of metal lithium battery interface, significantly improved lithium deposition/ Dipping current density and Kuron efficiency.

CN119340336APending Publication Date: 2025-01-21CHONGQING AEROSPACE POLYTECHNIC COLLEGE
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411522052.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

Metal lithium batteries face the safety challenges of lithium dendrites and the low efficiency of Coulombs, and the interface resistance and instability of garnet-type oxide electrolytes with metal lithium limit their application.

Method used

By covering fluoropromic acid on oxide electrolytes, a combination layer of mutual erosion is formed, the interface resistance is reduced, and the lf -lithium is combined with melting lithium to form a high -interface LIF and high -conductive LI3P interface.

Benefits of technology

It significantly increased the density of lithium sedimentary/peeling current to 10mA/CM2, and Kuron's efficiency was increased to more than 99 %, extending the cycle life of the battery, and reducing production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119340336A_ABST
    Figure CN119340336A_ABST
Patent Text Reader

Abstract

The invention discloses a metal lithium composite electrolyte negative electrode, a preparation method and application, and relates to the field of new material preparation and energy. Two-dimensional surface contact of an oxide electrolyte and metal lithium in the prior art is upgraded to three-dimensional body contact of the oxide electrolyte and the metal lithium, so that the oxide electrolyte / metal lithium interface resistance is reduced, the interface battery distribution is homogenized, the lithium deposition / stripping current density is remarkably improved from 1.0 mA / cm < 2 > to 10mA / cm < 2 >, the lithium cycle coulombic efficiency is improved to 99% or above, and the lithium battery performance is improved. And a foundation is laid for the development of a high-energy-density fast-charging metal lithium battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of new material preparation and energy, and in particular to a metal lithium composite electrolyte negative electrode, a preparation method and application thereof. Background Art

[0002] With the rapid development of new energy vehicles, communication equipment, aerospace equipment, ships and other fields, commercial lithium-ion batteries using graphite negative electrodes can no longer meet application requirements. There is an urgent need to develop new energy storage technologies with high energy density, high power density, long cycle life and high safety. Metallic lithium has an ultra-high theoretical specific capacity of 3860mAh / g, an extremely low electrochemical potential of -3.04V, and an ultra-light density of 0.535g / cm3. It is considered to be the ultimate negative electrode material for batteries. Metallic lithium batteries are expected to bring revolutionary improvements to battery energy density. However, the safety challenge of lithium dendrites and the limitation of low coulombic efficiency faced by metallic lithium negative electrodes are the two main problems restricting their commercial applications.

[0003] Garnet-type oxide electrolytes have the advantages of high ionic conductivity, electronic insulation, high mechanical strength, good electrochemical stability, and safety. They are expected to be used in lithium metal batteries to solve the challenges faced by lithium metal, and have received extensive attention and research at home and abroad. Despite this, the large interface resistance and interface instability between garnet-type oxide electrolytes and lithium metal are still huge obstacles to their application. The solid-solid interface "point contact" between garnet-type oxide electrolytes and lithium metal will induce lithium to preferentially nucleate and grow at certain sites to form lithium dendrites, and then gradually grow towards the grain boundaries, pores, microcracks and other defective areas of the oxide electrolyte, resulting in short circuits. Therefore, it is particularly critical to regulate the interface contact between garnet-type oxide electrolytes and lithium metal.

[0004] In response to the above problems, one idea is to introduce a lithium-philic layer between the sintered dense garnet-type oxide electrolyte and metallic lithium. The prior art forms an aluminum oxide coating on the surface of a garnet-type electrolyte by atomic layer vapor deposition (ALD) to improve wettability with molten lithium and reduce the garnet-type electrolyte / metal lithium interface resistance (Nature Materials 2017, 16, 572). Prior art publication number CN117096423A discloses the use of ion beam deposition technology to coat a nanoscale metal chloride / fluoride coating on the surface of a dense garnet-type electrolyte, and then heats and reacts with metallic lithium. There is also a method for wetting a dense oxide electrolyte by reducing the surface tension of molten lithium disclosed in prior art publication number CN114678517B, adding silicon nitride to the molten lithium to wet the sintered dense garnet-type electrolyte.

[0005] The above methods generally involve the sintering and densification process of oxide solid electrolytes. Dense oxide electrolytes have many shortcomings: (1) The preparation temperature of oxide electrolytes is often above 1000°C, which leads to the volatilization of lithium salts, making it difficult to control the material composition and the consistency of material preparation poor. More importantly, the reaction with CO2 in the air leads to the formation of an inert layer of lithium carbonate on the surface of the oxide electrolyte, which inhibits the lithium affinity of the oxide electrolyte; (2) When using dense oxide electrolytes, the electrolyte faces the limitation of large thickness, which is actually often greater than 100μm. In addition, the density of oxide electrolytes is generally high, which seriously limits the mass energy density of the battery; (3) Dense oxide electrolytes are brittle and difficult to process. Moreover, the above methods involve the interface between the oxide electrolyte and metallic lithium as "two-dimensional surface contact", and the contact area is still limited, resulting in the lithium deposition / stripping current density generally being lower than 1.0mA / cm 2 ; In addition, the above method involves complex coating preparation technology and is costly. Summary of the invention

[0006] In view of the above-mentioned deficiencies in the prior art, the present invention provides a solid-liquid hybrid metal lithium battery and a preparation method thereof, which can realize the wetting of metal lithium on oxide electrolyte particles, and simultaneously generate an interface phase of LiF with high interfacial energy for metal lithium and Li3P with high conductivity, thereby improving the lithium deposition / stripping current density and coulombic efficiency.

[0007] In order to achieve the above-mentioned object of the invention, the technical solution adopted by the present invention is:

[0008] Provided is a metal lithium composite electrolyte negative electrode, which is obtained by coating an oxide electrolyte with a fluorine-containing phosphonic acid and then combining it with molten lithium;

[0009] The oxide electrolyte coated with fluorine-containing phosphonic acid forms a mutually corroded bonding layer at the junction with the molten lithium, thereby reducing the interface resistance and uniformizing the current distribution.

[0010] The present invention also provides a method for preparing the above-mentioned metal lithium composite electrolyte negative electrode, comprising the following steps:

[0011] S1: drying the oxide electrolyte, heat treating it at 700-1000°C for 5-24h, and ball milling it to obtain a powdered oxide electrolyte;

[0012] S2: dissolving the fluorine-containing phosphonic acid in a solvent to obtain a fluorine-containing phosphonic acid functional liquid;

[0013] S3: dispersing the oxide electrolyte into the fluorine-containing phosphonic acid functional liquid, stirring for 0-2 hours at a temperature not higher than the boiling point of the fluorine-containing phosphonic acid, to obtain an electrolyte grafted with the fluorine-containing phosphonic acid;

[0014] S4: Covering the surface of the metal lithium foil with the electrolyte grafted with fluorine-containing phosphonic acid, heating to 200-400° C., and keeping the temperature for 30-300 min to obtain a metal lithium composite electrolyte negative electrode.

[0015] Furthermore, the oxide electrolyte is a non-sintered dense powdered oxide electrolyte, including a combination of one or more of a garnet-type electrolyte, a sodium fast ion conductor-type electrolyte, a perovskite-type electrolyte, and a lithium fast ion conductor-type electrolyte.

[0016] Furthermore, the fluorine-containing phosphonic acid is an organic acid having a stable phosphate group and a fluorine atom.

[0017] Furthermore, the fluorine-containing phosphonic acid is monofluorophosphoric acid or 1H,1H,2H,2H-perfluorooctanephosphonic acid.

[0018] Furthermore, in step S2, the solvent is deionized water, and the concentration of the fluorine-containing phosphonic acid in the fluorine-containing phosphonic acid functional liquid is 1-20%.

[0019] Furthermore, the thickness of the electrolyte layer on the metal lithium composite electrolyte negative electrode is 5-10 μm.

[0020] The present invention also provides an application of the above-mentioned metal lithium composite electrolyte negative electrode in the preparation of a solid-liquid mixed metal lithium battery, characterized in that the solid-liquid mixed metal lithium battery comprises a positive electrode sheet, a carbonate organic electrolyte, a diaphragm and a metal lithium composite electrolyte negative electrode;

[0021] The preparation method of the positive electrode sheet is specifically as follows: the positive electrode material, the conductive agent and the binder are mixed into a slurry, the slurry is coated on an aluminum current collector, and then dried.

[0022] Furthermore, the positive electrode material is a nickel-cobalt-manganese ternary material, lithium iron phosphate or lithium cobalt oxide, the conductive agent is a combination of one or more of SP, CNTs and graphene, and the binder is a combination of one or more of PVDF, CMC and SBR.

[0023] Furthermore, the mass ratio of the positive electrode material, the conductive agent and the binder is 80-96:2-10:2-10.

[0024] The beneficial effects of the present invention are:

[0025] 1. The present invention uses powdered granular oxide electrolyte to construct an integrated metal lithium composite electrolyte negative electrode, upgrading the "two-dimensional surface contact" of oxide electrolyte and metal lithium in the prior art to "three-dimensional body contact" of oxide electrolyte and metal lithium, thereby reducing the oxide electrolyte / metal lithium interface resistance, homogenizing the interface battery distribution, and the lithium deposition / stripping current density from 1.0 mA / cm 2 Significantly increased to 10mA / cm 2The lithium cycle coulomb efficiency has been increased to more than 99%, laying the foundation for the development of high energy density and fast charging metal lithium batteries.

[0026] 2. The present invention uses powdered granular oxide electrolyte to construct a "three-dimensional contact" between the oxide electrolyte and metallic lithium, which not only increases the interface contact area between the solid electrolyte and metallic lithium, but also during the battery cycle, the powdered granular oxide electrolyte cooperates with the volume change of the metallic lithium negative electrode to maintain good interface contact, thereby improving battery life.

[0027] 3. The method of the present invention is simple and easy to implement, does not require expensive equipment, does not require high temperature, and is time-saving. It only requires soaking the oxide electrolyte in a specific fluorine-containing phosphonic acid functional liquid, and then reacting chemically with metallic lithium. The resulting solid-liquid mixed metal lithium battery has excellent performance and is conducive to large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 is the X-ray diffraction pattern of PFOPA-LLZO particles prepared in Example 1;

[0029] Figure 2 The high-resolution transmission electron microscope and energy spectrum diagram of the PFOPA-LLZO particles prepared in Example 1;

[0030] Figure 3 This is a scanning electron microscope image of the metal lithium composite electrolyte negative electrode prepared in Example 1;

[0031] Figure 4 This is a scanning electron microscope image of the metal lithium composite electrolyte negative electrode prepared in Example 2;

[0032] Figure 5 This is a scanning electron microscope image of the metal lithium composite electrolyte negative electrode prepared in Example 3;

[0033] Figure 6 The lithium deposition / stripping current density test curves of each group of lithium symmetric batteries prepared in Example 4;

[0034] Figure 7 The lithium cycle coulomb efficiency test comparison curve of each group of lithium-copper batteries prepared in Example 4;

[0035] Figure 8 This is the charge and discharge cycle curve of the solid-liquid mixed metal lithium battery prepared in Experimental Group 2;

[0036] Fig. 9 The charge and discharge cycle curve of the solid-liquid mixed metal lithium battery prepared in Comparative Example 3;

[0037] Fig.10This is a charge and discharge cycle curve of the solid-liquid mixed metal lithium battery prepared in Comparative Example 4. DETAILED DESCRIPTION

[0038] The specific implementation modes of the present invention are described below so that those skilled in the art can understand the present invention. However, it should be clear that the present invention is not limited to the scope of the specific implementation modes. For those of ordinary skill in the art, as long as various changes are within the spirit and scope of the present invention as defined and determined by the attached claims, these changes are obvious, and all inventions and creations utilizing the concept of the present invention are protected.

[0039] Example 1

[0040] In this embodiment, a cubic garnet electrolyte Li 6.5 Ln3Z 1.5 Ta 0.5 O 12 The powder (LLZO) is prepared by a solid phase synthesis method known in the art. In other embodiments of the present invention, a sodium fast ion conductor electrolyte, a perovskite electrolyte or a lithium fast ion conductor electrolyte may be used; or a combination of a garnet electrolyte, a sodium fast ion conductor electrolyte, a perovskite electrolyte, and a lithium fast ion conductor electrolyte may be used.

[0041] The LLZO powder was cooled to 200°C in a muffle furnace and then taken out, and then ground in isopropanol using a zirconium oxide ball mill and ball mill for 12 hours at a ball mill speed of 600 rpm and 100°C, and dried in a vacuum oven for 12 hours;

[0042] The fluorine-containing phosphonic acid functional liquid is prepared by dissolving 1H, 1H, 2H, 2H-perfluorooctanephosphonic acid (PFOPA) in deionized water and fixing the volume to a PFOPA concentration of 10% to obtain the PFOPA functional liquid. In specific implementation, the fluorine-containing phosphonic acid functional liquid can also use monofluorophosphoric acid.

[0043] Take 10g of the dried LLZO powder and place it in 20ml of PFOPA functional solution. Stir it at room temperature for 5 minutes. The phosphoric acid groups of 1H,1H,2H,2H-perfluorooctanephosphonic acid will react with the Li + The ions reacted with each other to obtain LLZO particles with 1H, 1H, 2H, 2H-perfluorooctanephosphonic acid grafted on the surface (PFOPA-LLZO particles). X-ray diffraction analysis of PFOPA-LLZO particles showed the following results: Figure 1 As shown by Figure 1 It can be seen that after the LLZO particles were functionalized with PFOPA functional liquid, the garnet cubic crystal form of LLZO remained unchanged, indicating that PFOPA did not affect the crystal phase of LLZO.

[0044] The PFOPA-LLZO particles were tested using a high-resolution transmission electron microscope (JSM-7800F) from Japan Electronics. Figure 2 As shown, Figure 2 a is the electron microscope image of PFOPA-LLZO particles. Figure 2 b is the energy spectrum of La and P elements in PFOPA-LLZO particles. Figure 2 c is the energy spectrum of Zr and F elements in PFOPA-LLZO particles; Figure 2 It can be seen that the size of PFOPA-LLZO particles is about 150nm. After the LLZO powder is treated with PFOPA functional liquid for 5 minutes, a PFOPA coating layer with a thickness of about 10nm is formed on the LLZO surface; La element is the main component element of LLZO, and P element is the main component element of PFOPA. It can be clearly found that the P element is evenly distributed around the La element, indicating that PFOPA is evenly coated on the surface of LLZO nanoparticles; Zr element is the main component element of LLZO, and F element is the main component element of PFOPA. It can be clearly found that the F element is evenly distributed around the Zr element, further indicating that PFOPA is evenly coated on the surface of LLZO nanoparticles.

[0045] In an inert environment, the prepared LLZO particles with 1H, 1H, 2H, 2H-perfluorooctanephosphonic acid grafted on the surface are covered on a 100 μm thick metal lithium sheet, heated to 300°C and kept warm for 0.5 h to complete the reaction of 1H, 1H, 2H, 2H-perfluorooctanephosphonic acid with metal lithium, achieve wetting of the oxide electrolyte particles by molten lithium, and obtain a metal lithium composite electrolyte negative electrode.

[0046] The metal lithium composite electrolyte negative electrode was tested using a high-resolution transmission electron microscope. Figure 3 The electron microscope image shown is from Figure 3 It can be seen that the electrolyte layer on the surface of metallic lithium is dense and has a thickness of about 10 microns. Compared with the conventional composite method of the prior art, the electrolyte layer prepared by the prior art has a clear boundary with metallic lithium, while the electrolyte layer prepared by the composite method adopted in the present invention and metallic lithium produce a "mutual erosion" effect, forming a three-dimensional surface contact, which can increase the contact area.

[0047] Example 2

[0048] The difference between this embodiment and embodiment 1 is that after the LLZO particles with 1H, 1H, 2H, 2H-perfluorooctanephosphonic acid grafted on the surface are covered on a 100 μm thick metal lithium sheet, the metal lithium composite electrolyte negative electrode is prepared by heating to 300° C. and keeping the temperature for 1.0 h.

[0049] The metal lithium composite electrolyte negative electrode was tested using a high-resolution transmission electron microscope. Figure 4 The electron microscope image shown is from Figure 4 It can be seen that the thickness of the electrolyte layer on the surface of the metal lithium is about 9 microns, the electrolyte layer is dense at the contact with the metal lithium, and the surface of the electrolyte layer away from the metal lithium is looser than that of Example 1. Different reaction times will not affect the thickness of the electrolyte layer, but will significantly change the microscopic morphology of the electrolyte layer, which will become looser.

[0050] Example 3

[0051] The difference between this embodiment and embodiment 1 is that when preparing LLZO particles with 1H,1H,2H,2H-perfluorooctanephosphonic acid grafted on the surface, 10 g of LLZO powder after drying is placed in 20 ml of PFOPA functional liquid and stirred at room temperature for 10 minutes.

[0052] The metal lithium composite electrolyte negative electrode was tested using a high-resolution transmission electron microscope. Figure 5 The electron microscope image shown is from Figure 5 It can be seen that the electrolyte layer on the surface of metallic lithium is looser than that in Example 2, and has a thickness of about 9 microns, indicating that the treatment time of LLZO nanoparticles in 1H, 1H, 2H, 2H-perfluorooctanephosphonic acid functional liquid will affect the reaction between the electrolyte and metallic lithium, thereby affecting the microscopic morphology of the electrolyte layer in the metallic lithium composite electrolyte negative electrode.

[0053] Example 4

[0054] The metal lithium composite electrolyte negative electrode prepared in Example 1 was used to assemble a lithium symmetric battery and a lithium copper battery, respectively, as experimental group 1, using 5 μm PE as a separator, and the electrolyte was prepared by dissolving 1 mol / L LiTFSI in a mixed solvent of DME and DOL, the volume ratio of DME and DOL in the mixed solvent was 1:1, LiNO3 was added to a fixed volume of 2% by mass, and the amount of electrolyte was 10 μL.

[0055] The electrodes on both sides of the lithium symmetrical battery are both metal lithium composite electrolyte negative electrodes, and the electrode on one side of the lithium copper battery is a metal lithium composite electrolyte negative electrode, and the electrode on the other side is copper foil.

[0056] Set up comparative example 1: The difference between comparative example 1 and experimental group 1 is that metallic lithium is used to assemble a lithium symmetric battery and a lithium copper battery respectively, and other parameters are consistent with experimental group 1.

[0057] Set up comparative example 2: The difference between comparative example 2 and experimental group 1 is that LLZO particles are covered on a 100 μm thick metal lithium sheet, heated to 300°C, and kept warm for 0.5 h to obtain a comparative negative electrode, and the comparative negative electrode is used to assemble a lithium symmetric battery and a lithium copper battery respectively. The other parameters are consistent with experimental group 1.

[0058] The lithium symmetric batteries prepared in Experimental Group 1, Comparative Example 1 and Comparative Example 2 were tested for lithium deposition / stripping current density. The test results are as follows: Figure 6 As shown, Figure 6 a is the lithium deposition / stripping current density test curve of the lithium symmetric battery in comparative example 1, Figure 6 b is the lithium deposition / stripping current density test curve of the lithium symmetric battery in comparative example 2, Figure 6 c is the lithium deposition / stripping current density test curve of the lithium symmetric battery in experimental group 1; Figure 6 It can be seen that the critical current density of the short circuit of the lithium symmetric battery prepared in Comparative Example 1, Comparative Example 2, and Experimental Group 1 is 10 mA / m 2 , 12mA / m 2 , 13mA / m 2 . It is explained that, compared with the original metallic lithium negative electrode (Comparative Example 1), the current density of lithium dendrites produced by directly compounding LLZO without any treatment with metallic lithium (Comparative Example 2) is higher. This is because the present invention designs a stable LLZO electrolyte protection layer on the surface of metallic lithium foil, thereby isolating the corrosion of the electrolyte to the lithium foil and improving the stability of the lithium negative electrode. Furthermore, compared with directly compounding LLZO without any treatment with metallic lithium (Comparative Example 2), the metallic lithium composite electrolyte negative electrode obtained by treating LLZO with PFOPA and compounding it with metallic lithium (Experimental Group 1) is more stable and less likely to produce lithium dendrites. This is because the present invention further designs a PFOPA coating on the surface of LLZO, and PFOPA reacts with metallic lithium to generate lithium phosphide and lithium fluoride, further improving the stability of the lithium negative electrode.

[0059] The lithium copper batteries prepared in Experimental Group 1, Comparative Example 1 and Comparative Example 2 were tested for lithium cycle coulombic efficiency. The test results are as follows: Figure 7 As shown by Figure 7It can be seen that the coulombic efficiencies of the lithium-copper batteries obtained in Comparative Example 1, Comparative Example 2, and Experimental Group 1 are 98.5%, 99.1%, and 99.8%, respectively. It is shown that, relative to the original metal lithium negative electrode (Comparative Example 1), the use of LLZO without any treatment directly composited with metal lithium (Comparative Example 2) results in a higher electrochemical reversibility of the obtained lithium negative electrode. This is because the present invention designs a stable LLZO electrolyte protective layer on the surface of the metal lithium foil, thereby isolating the corrosion of the electrolyte to the lithium foil and improving the electrochemical reversibility of lithium. Further, relative to the use of LLZO without any treatment directly composited with metal lithium (Comparative Example 2), the use of PFOPA to treat LLZO and composite with metal lithium (Experimental Group 1) further improves the electrochemical reversibility of the metal lithium composite electrolyte negative electrode. This is because the present invention further designs a PFOPA coating on the surface of LLZO, and PFOPA reacts with metal lithium to generate lithium phosphide and lithium fluoride, further improving the electrochemical reversibility of the lithium negative electrode.

[0060] Example 5

[0061] The solid-liquid mixed metal lithium battery was prepared using the metal lithium composite electrolyte negative electrode prepared in Example 1 as Experimental Group 2, specifically:

[0062] A1: The positive electrode material NCM811, the conductive agent SP, and the binder PVDF were mixed into a slurry in a mass ratio of 90:5:5, and then coated on the aluminum current collector. After drying, the positive electrode sheet was obtained. The diameter of the positive electrode sheet was 10 mm, and the active material loading was 18 mg / cm 2 .

[0063] A2: Cover the metal lithium composite electrolyte negative electrode with a 5μm thick PE separator;

[0064] A3: Add carbonate organic electrolyte on the side of the PE diaphragm away from the metal lithium composite electrolyte negative electrode. The carbonate organic electrolyte composition is 0.05 mol / L LiPF6, 0.6 mol / L LiTFSI and 0.4 mol / L LiBOB-EC-EMC. The amount of electrolyte is 10 μL.

[0065] LiBOB-EC-EMC is a solution of lithium bis(oxalatoborate), ethylene carbonate and ethyl methyl carbonate in a volume ratio of 1:1:1.

[0066] A4: Cover with a positive electrode sheet, add a steel sheet, and encapsulate the button battery shell. After a static aging process of about 12 hours, the solid-liquid mixed metal lithium battery of the present invention is obtained.

[0067] Set up comparative example 3: The difference between comparative example 3 and experimental group 2 is that metallic lithium is used as the negative electrode to prepare a solid-liquid mixed metal lithium battery, and other parameters are consistent with experimental group 2.

[0068] Set up comparative example 4: The difference between comparative example 4 and experimental group 2 is that a solid-liquid mixed metal lithium battery is prepared by using a negative electrode compared with comparative example 2, and other parameters are consistent with experimental group 2.

[0069] The solid-liquid mixed metal lithium batteries prepared in Comparative Example 3, Comparative Example 4 and Experimental Group 2 were subjected to charge and discharge cycle tests respectively. The test results are as follows: Figure 8-10 As shown, Figure 8 The left side shows the cycle curve of the solid-liquid mixed metal lithium battery prepared in experimental group 2. Figure 8 The right side shows the voltage-capacity curve of the solid-liquid hybrid metal lithium battery prepared in experimental group 2;

[0070] Fig. 9 The left side is the cycle curve of the solid-liquid mixed metal lithium battery prepared in Comparative Example 3. Fig. 9 The right side is the voltage-capacity curve of the solid-liquid mixed metal lithium battery prepared in Comparative Example 3;

[0071] Fig.10 The left side is the cycle curve of the solid-liquid mixed metal lithium battery prepared in Comparative Example 4. Fig.10 The right side is the voltage-capacity curve of the solid-liquid mixed metal lithium battery prepared in Comparative Example 4.

[0072] Depend on Figure 8-10 It can be seen that the experimental group 2 was charged and discharged at a rate of 0.3C and discharged at a rate of 0.5C. The first discharge capacity was 181 mAh / g. After 150 cycles, the capacity retention rate was 90%.

[0073] In comparative example 3, the battery was charged and discharged at a rate of 0.3C and discharged at a rate of 0.5C. The first discharge capacity was 173 mAh / g and the cycle life was 90 cycles.

[0074] In comparative example 4, the battery was charged and discharged at a rate of 0.3C and discharged at a rate of 0.5C. The first discharge capacity was 172 mAh / g and the cycle life was 120 cycles.

[0075] In summary, the lithium cycle coulombic efficiency of the solid-liquid mixed metal lithium battery prepared by the PFOPA-LLZO particles proposed in the present invention and the metal lithium composite electrolyte negative electrode made from molten lithium is increased to more than 99%, and the cycle life is significantly improved, which lays the foundation for the development of high energy density fast-charging metal lithium batteries.

Claims

1. A metal lithium composite electrolyte negative electrode, characterized in that: The metal lithium composite electrolyte negative electrode is obtained by coating an oxide electrolyte with a fluorine-containing phosphonic acid and then combining it with molten lithium; The oxide electrolyte coated with fluorine-containing phosphonic acid forms a mutually corroded bonding layer at the junction with the molten lithium, thereby reducing the interface resistance and uniformizing the current distribution.

2. A method for preparing a metal lithium composite electrolyte negative electrode according to claim 1, characterized in that: The steps include: S1: drying the oxide electrolyte, heat treating it at 700-1000°C for 5-24h, and ball milling it to obtain a powdered oxide electrolyte; S2: dissolving the fluorine-containing phosphonic acid in a solvent to obtain a fluorine-containing phosphonic acid functional liquid; S3: dispersing the oxide electrolyte into the fluorine-containing phosphonic acid functional liquid, stirring for 0-2h at a temperature not higher than the boiling point of the fluorine-containing phosphonic acid, to obtain an electrolyte grafted with the fluorine-containing phosphonic acid; S4: Covering the surface of the metal lithium foil with the electrolyte grafted with fluorine-containing phosphonic acid, heating to 200-400° C., and keeping the temperature for 30-300 min to obtain a metal lithium composite electrolyte negative electrode.

3. The preparation method according to claim 2, characterized in that: The oxide electrolyte is a non-sintered dense powdered oxide electrolyte, including a combination of one or more of a garnet-type electrolyte, a sodium fast ion conductor-type electrolyte, a perovskite-type electrolyte, and a lithium fast ion conductor-type electrolyte.

4. The preparation method according to claim 2, characterized in that: The fluorine-containing phosphonic acid is an organic acid having a stable phosphoric acid group and a fluorine atom.

5. The preparation method according to claim 4, characterized in that: The fluorine-containing phosphonic acid is monofluorophosphoric acid or 1H,1H,2H,2H-perfluorooctanephosphonic acid.

6. The preparation method according to claim 2, characterized in that: In the step S2, the solvent is deionized water, and the concentration of the fluorine-containing phosphonic acid in the fluorine-containing phosphonic acid functional liquid is 1-20%.

7. The preparation method according to claim 2, characterized in that: The thickness of the electrolyte layer on the negative electrode of the metal lithium composite electrolyte is 5-10 μm.

8. The use of the metal lithium composite electrolyte negative electrode according to claim 1 in the preparation of a solid-liquid mixed metal lithium battery, characterized in that: The solid-liquid mixed metal lithium battery comprises a positive electrode, a carbonate organic electrolyte, a separator and a metal lithium composite electrolyte negative electrode; The preparation method of the positive electrode sheet is specifically as follows: the positive electrode material, the conductive agent and the binder are mixed into a slurry, the slurry is coated on an aluminum current collector, and then dried.

9. The use according to claim 8, characterized in that: The positive electrode material is a nickel-cobalt-manganese ternary material, lithium iron phosphate or lithium cobalt oxide, the conductive agent is a combination of one or more of SP, CNTs and graphene, and the binder is a combination of one or more of PVDF, CMC and SBR.

10. The use according to claim 8, characterized in that: The mass ratio of the positive electrode material, the conductive agent and the binder is 80-96:2-10:2-10.

Citation Information

Patent Citations

  • A molten lithium battery anode material, its preparation method, and an all-solid-state lithium battery

    CN114678517B

  • Method for constructing garnet-based solid electrolyte surface interface layer at low temperature, application and all-solid-state lithium metal battery

    CN117096423A